Exploring the Relationship Between Interest Rates and Bank Profitability in Financial Institutions - Andino Tavakoli; Partosoebroto (Indonesia Accounting Research Journal, 2023)
This research delves into the intricate relationship between interest rates and bank profitability, aiming to unravel the dynamics, mechanisms, and implications of this critical nexus. Drawing upon empirical evidence, theoretical frameworks, and practical insights, the study investigates the impact of interest rate changes on banks' net interest margins, loan demand, credit quality, and non-interest income streams. Through a systematic analysis of data sources, analytical techniques, and theoretical constructs, we elucidate the heterogeneity across banks in their sensitivity to interest rate fluctuations, considering factors such as business models, market segments, and regulatory environments. The findings of this research hold significant implications for policymakers, financial institutions, investors, and regulators, informing decision-making, risk management, and strategic planning in response to interest rate dynamics. While the study provides valuable insights, it also identifies avenues for future research, including exploring macroprudential implications, fintech disruptions, sustainability considerations, and methodological challenges. As we navigate the evolving landscape of finance and banking, interdisciplinary collaboration, methodological innovation, and stakeholder engagement will be essential for advancing knowledge and fostering resilience within the financial system.